2021
DOI: 10.1055/s-0041-1722929
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal Symptoms and Self-Reported Health before and after Endoscopic Pituitary Surgery—A Prospective Study

Abstract: Objectives Despite the limited invasiveness of endoscopic transsphenoidal surgery (ETSS), some degree of nasal structure destruction is unavoidable. Our objective was to evaluate sinonasal morbidity and self-reported health before and 6 months after ETSS for pituitary tumors, and to identify possible predictive factors for deterioration in sinonasal health. Design Prospective observational cohort study. Setting University tertiary referral hospital. Participants Totally 109 consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Moreover, negative effects of extended surgical intervention on SNH have already been reported for the Hadad septal flap ( 19 ). In addition, Hallén et al and Chmielewski et al reported that previous nasal surgery might be a risk factor for decreased SNH after endoscopic pituitary adenomectomy ( 20 , 21 ) underlining the role of unaffected mucosa for SNH.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, negative effects of extended surgical intervention on SNH have already been reported for the Hadad septal flap ( 19 ). In addition, Hallén et al and Chmielewski et al reported that previous nasal surgery might be a risk factor for decreased SNH after endoscopic pituitary adenomectomy ( 20 , 21 ) underlining the role of unaffected mucosa for SNH.…”
Section: Discussionmentioning
confidence: 99%
“…Embase and MEDLINE databases were interrogated with the search phrase [(“endoscopic endonasal” OR “endoscopic transsphenoidal”) AND (“nasal morbidity” OR “sino-nasal outcome” OR “sino-nasal outcome test 22”)]. 12 contemporary papers were identified [ 3 , 5 , 8 , 9 , 14 21 ]. Scagnelli et al demonstrated that overall SNOT-22 scores followed the expected rise and fall pattern after endoscopic transsphenoidal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Each patient graded their perceived health status before and at 12-months after TSS on a 101-point scale (0 = "the worst health you can imagine"; 100 = "the best health you can imagine"). The EQ-5D is commonly used by clinical researchers to evaluate QoL [24] and treatment effects, including those in patients with pituitary tumors [25,26] and headache [27,28].…”
Section: Qol Assessmentmentioning
confidence: 99%